AKTIVITAS FARMAKOLOGI DAN FITOKIMIA AKAR, TANGKAI DAUN, BUAH, DAN BIJI AREN (Arenga pinnata) : REVIEW TANAMAN OBAT - Herawati Eliah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
The palm tree is a tree originating from Southeast Asia which belongs to the Aracecae family. Sugar palm is a plant that can be used to treat diseases. Palm fruit is rich in fiber (16.2%), protein (10.0%), minerals (7.9%), and (1.5%) fat. Roots, petioles, fruit, and palm seeds have pharmacological activity. According to several previous studies, palm root has activity as a diuretic. Then the palm leaf stalk has activity as a sunscreen. In addition, palm fruit seeds have antimicrobial activity and palm fruit itself has antioxidant, antidiabetic, anti-inflammatory, analgesic, and antiphotoaging activities.